Pengembangan Media Game Edukasi Cerita Rakyat Berjudul Wiro Sableng menggunakan RPG Maker MV - Muhammad Rizky Aditya Rhamadhan; Heri Haerudin (CV. Multi Kreasi Media, 2024)
Indonesia has a lot of international cultural diversity which has its own uniqueness and characteristics, a researcher wants to try different learning methods in AL-MUARIF Kindergarten by using RPG Maker MV to make an educational game about folklore. To create an educational game for the folklore of Wiro Sableng, the authors use the Game Development Life Cycle (GDLC) method which is the right way and has good procedures for making games. Wiro Sableng's folklore was chosen because it has various types of education, simulation, and entertainment that can assist teachers in teaching children about folklore. This folklore educational game will be very useful in the child's learning process.